1995
DOI: 10.1007/bf01972973
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of Ringer solution versus serum for partial exchange transfusion in neonatal polycythaemia

Abstract: PET with Ringer solution resulted in a haemodilution comparable to PET with serum and a correction of hypervolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…(52), comparing plasma to NS, Roithmaier et al. (53) comparing plasma to Ringer lactate, Wong et al. (54) comparing albumin to NS, Krishnan and Rahim (55) comparing plasma to NS, and Jan et al.…”
Section: Technical Aspects Of Petmentioning
confidence: 99%
“…(52), comparing plasma to NS, Roithmaier et al. (53) comparing plasma to Ringer lactate, Wong et al. (54) comparing albumin to NS, Krishnan and Rahim (55) comparing plasma to NS, and Jan et al.…”
Section: Technical Aspects Of Petmentioning
confidence: 99%
“…In clinical settings, PET is commonly administered when hematocrit exceeds 69% or in symptomatic neonates with hematocrit of !65%. 17,18 In the present study, asymptomatic neonates with hematocrit of 65 to 69% were conservatively observed, and those with hematocrit of 70 to 75% were treated with IV fluids and NPO. PET was administered only when hematocrit exceeded 75% or when early symptoms occurred.…”
Section: Discussionmentioning
confidence: 82%
“…16 In clinical settings, however, PET is commonly performed when hematocrit exceeds 69% or in symptomatic neonates with hematocrit !65%. 17,18 This approach is based on studies that have shown an association between polycythemia and impaired long-term developmental outcome as well as on those in which PET has been shown to reduce pulmonary vascular resistance and increase cerebral blood flow. 2,3,19 Nevertheless, PET has not been shown to improve long-term developmental or neurological outcomes.…”
mentioning
confidence: 99%
“…We identified a total of six studies which appeared to be randomized, controlled trials of a crystalloid solution versus a colloid solution for partial exchange transfusion (Torre 1988 [11], Deorari 1995 [12], Roithmaier 1995 [13], Wong 1997 [14], Krishnan 1997 [15], and Supapannachart 1999 [16]) in the polycythemic newborn.…”
Section: Resultsmentioning
confidence: 99%